Contemporary approach to prevention and therapy of the no-reflow phenomenon - Stajić, Zoran; Panić, Sunčica; Davidović, Goran (PONS - medicinski časopis, 2024)
No-reflow phenomenon is defined as a state of inadequate (incomplete) myocardial perfusion through a certain segment of the coronary circulation, in the absence of mechanical obstruction of the epicardial coronary artery, i.e. without the presence of significant residual stenosis, spasm, occlusive dissection or intracoronary thrombosis. The development of the no-reflow phenomenon in patients with acute myocardial infarction with ST elevation increases the risk of early clinical complications and mortality many times over. Early intrahospital complications are manifested in the form of hemodynamic instability, acute heart failure including cardiogenic shock, myocardial rupture, and arise as a result of the extension of the area of myocardial necrosis, malignant cardiac arrhythmias, conduction disorders and acute pulmonary edema. The aim of this review is to present the modern aspects of prevention and therapeutic possibilities in patients with the developed no-reflow phenomenon. Prevention involves the application of various strategies before the complete reopening of the occluded infarcted coronary artery, with the aim of preparing the coronary microcirculation for reperfusion. Preventive measures should be directed towards different pathophysiological mechanisms of the no-reflow phenomenon in order to be effective, from the reduction of the total ischemic time, to the application of various pharmacological and non-pharmacological measures. Application of therapeutic measures is necessary in case of unsuccessful prevention and development of no-reflow phenomenon. In this context, therapeutic agents should be effective during current and progressive myocardial circulation damage, and the modern method of primary percutaneous coronary intervention provides the possibility of delivering high local doses of pharmacological agents directly to the infarcted coronary artery, unlike traditional treatment using fibrinolytic therapy.
Keywords: no-reflow; acute myocardial infarction; ST elevation; primary percutaneous coronary intervention; reperfusion.